SOIL CREEP IN BALEKAMBANG, CIRAWAMEKAR, CIPATAT DISTRICT, BANDUNG BARAT REGENCY, WEST JAVA - Tejakusuma, Iwan Gunawan (Jurnal Sains dan Teknologi Mitigasi Bencana, 2018)
Soil creep occurred in Balekambang, Cirawamekar, Cipatat, West Bandung Regency, West Java. This area is karst hill consist of limestone with interbedded sediment in the valley. The limestone is interfingered with clay, marl and quartz sandstones. The clay and marl acting as the slipping plane with a steep dip of around 50o to 69o to the northwest. The direction of the slope movement approximately follows the direction of the bedding plane therefore the bedding plane control the soil creep. This landslide was triggered by rainfall which saturated the soil layer and environmental changes in the surrounding area.